Aplikasi Pembuatan Eco-Enzyme Berbahan Sampah Organik Di Lingkungan Kita - Wijayanti, Ruri; Anggia , Malse; Arziyah, Dewi; Yusmita, Lisa; Ariyetti, Ariyetti (CV. Information Technology Training Center - Indonesia (ITTC), 2021)
Waste is an environmental problem that continues to increase along with population growth and community consumption. Making eco-enzymes made by fermenting fruit and vegetable skins with brown sugar and water, is one of the organic waste processing processes that can be done at home. Through the making of eco-enzymes, this community service activity aims to increase community knowledge and ability in managing organic waste. This activity was carried out in Jawi-Jawi Village, Pariaman City. Where, community service activities were carried out by providing counseling and direct demonstrations. The results showed that the community was very enthusiastic and could immediately practice it that people better understand the benefits of eco-enzymes as natural cleaners and organic fertilizers. It is hoped that this event will build a community-based waste management culture.